FORMATION OF CREATIVE ABILITIES STUDENTS IN STUDY PEDAGOGICAL DISCIPLINES AT THE FACULTY OF ARTS AND GRAPHICS (Pedagogy of Higher and Secondary Education, 2022)
In article opportunities of formation of creative abilities of Undents are shown during teaching pedagogical disciplines at art-graphic faculty.
Keywords: creative capabilities; pedagogic